Prospection et évaluation des stocks de "petits bivalves" en Manche Est. Potentialités d'exploitation - Morin, Jocelyne (1998)
Surveys have been carried out from 1989 to 1991 in Eastern Channel, especially in "Baie de Seine". The objective was to complete the inventory of bivalves (Spisula ovalis, Tapes rhomboïdes and Glycymeris glycymeris) realized on the French coasts of North-East Atlantic and assess the potentialities of fishing exploitation in this area of the Channel. In the Eastern Channel, densities and biomasses are not very high and are much lower than thoses observed in West Cotentin. Spisula ovalis is not abundant and principally located in the sand zones of East and West of " Baie de Seine" and also near Dieppe-Le Tréport. Tapes rhomboïdes is more largely distributed in the whole "Baie de Seine". Although densities were more high than for Spisula ovalis, they are less high than in West Cotentin. This species is scarce in samples collected in Dieppe-Le Tréport area. Glycymeris glycymeris was not very present in the whole area prospected. In population structures, 10 age groups for Spisula ovalis, 9 for Tapes rhomboïdes have been identified. For these two species, the growth is important during the first three years. They reach respectively the mean size of 40 mm and 45 mm when they are three years old. Although some areas, among the most productive, could be accasionnally fished, exploitation possibilities of these bivalves appear to be limited in Eastern Channel. Les prospections réalisées de 1989 à 1991 en Manche Est, et plus particulièrement en baie de Seine, ont permis de compléter l'inventaire des ressources en "petits bivalves" (Spisula ovalis, Tapes rhomboïdes, Glycymeris glycymeris) réalisé sur les côtes françaises de l’Atlantique Nord-Est et d'en évaluer les potentialités d’exploitation dans ce secteur de la Manche. D’une façon générale en Manche Est, les densités et biomasses sont faibles et très inférieures à celles observées dans l’Ouest Cotentin. La spisule (Spisula ovalis) présente de faibles densités localisées principalement dans les zones sableuses de l’est et l’ouest de la baie de Seine et à proximité de ...